Dried Blood Spots, an Affordable Tool to Collect, Ship, and Sequence gDNA from Patients with an X-Linked Agammaglobulinemia Phenotype Residing in a Developing Country - Segundo, Gesmar R. S.; Nguyen, Anh T. V.; Thuc, Huyen T.; Nguyen, Le N. Q.; Kobayashi, Roger H.; Le, Hai T.; Le, Huong T. M.; Torgerson, Troy R.; Ochs, Hans D. (Frontiers in Immunology, 2018)
Background: New sequencing techniques have revolutionized the identification of the molecular basis of primary immunodeficiency disorders (PID), not only by establishing a gene-based diagnosis, but also by facilitating defect-specific treatment strategies, improving quality of life and survival, and allowing factual genetic counseling. Because these techniques are generally not available for physicians and their patients residing in developing countries, collaboration with overseas laboratories has been explored as a possible, albeit cumbersome, strategy. To reduce the cost of time- and temperature-sensitive shipping, we have selected Guthrie cards, developed for newborn screening, to collect dried blood spots (DBS) that can be shipped by regular mail at minimal cost. Method: Blood was collected and blotted onto the filter paper of Guthrie cards by completely filling three circles. We enrolled 20 male patients with presumptive X-linked Agammaglobulinemia (XLA) cared for at the Vietnam National Children's Hospital, their mothers and several sisters for carrier analysis. DBS were stored at room temperature until ready to be shipped together, using an appropriately sized envelope, to a CLIA-certified laboratory in the US for Sanger sequencing. The protocol for Sanger sequencing was modified to account for the reduced quantity of gDNA extracted from DBS. Result: High-quality gDNA could be extracted from every specimen. BTK mutations were identified in 17 of 20 patients studied, confirming the diagnosis of XLA in 85% of the study cohort. Type and location of the mutations were similar to those reported in previous reviews. The mean age when XLA was suspected clinically was 4.6 years, similar to that reported by Western countries. Two of 15 mothers, each with an affected boy, had a normal BTK sequence, suggesting gonadal mosaicism. Conclusion: DBS collected on Guthrie cards can be shipped inexpensively by airmail across continents, providing sufficient high-quality gDNA for Sanger sequencing overseas. Using this method of collecting gDNA we were able to confirm the diagnosis of XLA in 17 of 20 Vietnamese patients with the clinical diagnosis of agammaglobulinemia.